ANALISIS KARAKTERISTIK UNJUK KERJA KONDENSOR PADA SISTEM PENDINGIN (AIR CONDITIONING) YANG MENGGUNAKAN FREON R-134 a BERDASARKAN PADA VARIASI PUTARAN KIPAS PENDINGIN - Saut Siagian (Bina Teknika, 2015)
Air conditioning in the room is used to regulate humidity, heating and cooling the air in the room. This conditioning aims to provide comfort, so as to reducing fatigue. To get the air temperature corresponding to the desired lot alternative that can be applied, such as by increasing the heat transfer coefficient condensation and by adding the speed of cooling air in the condenser that will obtained coefficient greater performance. The method used in this study was experiments using the equipment of the machine refrigeration air conditioning system in the energy Conversion Laboratory designed by students of the faculty of Engineering , recorded data such as temperature, pressure and the pressure difference in the compressor. To make variations in condenser fan shaft rotation is done by making several changes to the motor frequency power move. Variations condenser fan rotation electric motor used is 50 rpm up to 120 rpm. The registration data such as pressure and temperature subsequently plotted on P-h chart for the refrigerant R-134a. Based on the discussion and the calculation of the data obtained, it can be a number of conclusions and performance characteristics of the cooling system, greater the flow rate air to cool the condenser then the coefficient of achievement is increasing. Because the rate of large heat release will impact on condenser temperatures are getting lower, so can achieve lower temperatures again in evaporator output. So the compressor work more light on the variation rate of heat release most.